EFFECTIVENESS OF HUMANITARIAN LOGISTICS OF RELIEF MATERIAL AT INTERNAL DISPLACED PERSONS CAMP IN ABUJA, NIGERIA - OHIDA, MUHAMMED ETUDAIYE; DABIN, KATMINA BOAZ; AJIBOYE, ARAOYE OLARINKOYE; ABUBAKAR, IBRAHIM DAMANA; GARBA, HASHIMU AUDI; YUSUF, NDAGI BABA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
Over the years, disasters have displaced millions of people and has forced many people into poverty. Hence, the need for humanitarian aids to provide care and relief items for the displaced person. The purpose of this study is to assess the effectiveness of humanitarian logistics of relief materials in selected internal displaced persons camp in Abuja. It formulated one null hypothesis stating, there is no statistically significance to the effectiveness of five key component of relief material logistics. Purposive sampling method was utilized to pick Malaysian Garden IDPs camp and Area one IDPs camp for this study. Conveniency sampling was utilized to administered 120 questionnaires among the humanitarian aids organization. Principal component factor analysis was used to reduce the variables into 5 key variables (i.e., Management of items in Inventory, Storage/warehousing of items, Distribution Approach, Procurement Method and available transport facilities). The data collected was analysed using descriptive statistics and inferential statistics; T test was utilized to test the hypothesis. The result shows that there is no statistically significance to the effectiveness of Management of items in inventory (P-value= 0.278); storage/Warehouse of items (P-value= 0.469), Distribution approach (P-value=0.371, Procurement method P-value =0.135) and available transport facilities (P-value = 0.142). The study recommends among others that adequate transport facilities should be provided by the government to aid swift mobility in the IDPs camps. Also, Relief items which are frequently demanded like drugs should be stored by the aid organization for easily delivery to the IDPs when needed.